Gibberellic acid-mediated transcriptional divergence underlies cold stress adaptation in two diploid cotton species - Dong Wang; Juyun Zheng; Ke Liu; Yanchao Xu; Dingsha Jin (PeerJ, 2025)
Background The diploid cotton species Gossypium thurberi (D1) and Gossypium trilobum (D8) exhibit significant divergence in cold stress tolerance despite their close phylogenetic relationship. Methods To explore the genetic basis of this difference, we conducted a comparative transcriptomic analysis under cold stress at 4 °C, identifying 697 and 311 species-specific differentially expressed genes (DEGs) in G. thurberi and G. trilobum, respectively. Functional enrichment analysis was performed to investigate the biological pathways associated with these DEGs. Additionally, hormone levels, particularly gibberellic acid (GA), were measured to assess their role in cold stress responses. Results The DEGs in both species were significantly enriched in the “hormone signal transduction” pathway, highlighting the importance of hormonal regulation in cold adaptation. Distinct trends in GA levels were observed between G. thurberi and G. trilobum, with GA strongly correlated with species-specific DEGs. G. thurberi demonstrated greater cold tolerance than G. trilobum, likely due to a more robust GA-regulated response. Conclusion These findings indicate that expression divergence in GA-mediated pathways between sister species has driven adaptive evolution in cold stress tolerance. This study not only advances our understanding of cold adaptation mechanisms in cotton but also provides genetic insights for improving cold tolerance in cultivated varieties through targeted breeding and genetic engineering.